Systemic immune inflammation index in differentiated thyroid cancers - Kars, Ayhan; Sakat, Muhammed Sedat; Sahin, Abdulkadir; Kılıc, Korhan; Bilen, Arzu (Pacini Editore, 2022)
The aim of this study was to investigate the relationship between differentiated thyroid carcinomas (DTCs), histopathological findings and systemic immune-inflammation index (SII) [neutrophil (N) x platelet (P) / lymphocyte (L)] values.93 patients with DTC were included. N, P and L levels were measured, and the relationship between the SII and histopathological findings was determined. The results were compared with the values of 33 healthy controls.SII values were significantly higher in the patient group than in the control group (p = 0.000). Tumour pathology diagnosis had no significant effect on SII (p = 0.90). Perineural lymphovascular and capsule invasion and extrathyroidal extension also had no significant effect on SII values. SII was significantly higher in patients with more than one tumour focus (p = 0.01). No significant relationship was determined between tumour diameter and SII.SII is higher in patients with DTC compared to the healthy population. High SII values may be associated with multifocality. According to the results of this study, SII does not affect the histological type, perineural, lymphovascular and capsule invasion, or extrathyroidal extension of DTC.
Keywords: Thyroid; Blood Platelets; Inflammation; Otorhinolaryngology; RF1-547; Neutrophils; Humans; Lymphocytes; Thyroid Neoplasms; Prognosis; Retrospective Studies